Doença de Alzheimer: intervenção psicoeducativa para familiares cuidadores - Neumann, Solange Maria Freire (2014)
Symptoms of depression, anxiety and burden are usually seen in family caregivers of people with dementia, compared with the general population . This research aimed to implement and evaluate the effects of a psychoeducational intervention, the rates of depression, anxiety and burden. We used a convenience sample consisting of fifteen family caregivers of patients with Alzheimer's disease and a strategy of quantitative and qualitative data. This is a study of quasi-experimental design, where we collected data on the same subject before and after the intervention. Were used as instruments: Depression Inventory and Beck Anxiety, Zarit Burden Interview, Sociodemographic Questionnaire, Satisfaction Questionnaire to assess the level of satisfaction of family caregivers and a semistructured interview to assess their impressions after the end of intervention, which consisted of eight group sessions in cognitive-behavioral approach. The results indicated that the intervention was effective to lower rates of depression and anxiety. However, there was no statistical significance in the rate of overhead. With regard to satisfaction with the intervention of family caregivers, it was established that was considered positive and that everyone would recommend to others who have a relative with the disease. Similarly, the qualitative analysis of the data confirms the quantitative results because the participants expressed satisfaction with the strategies and techniques learned. Despite the small sample size, the results suggest the effectiveness of the intervention. Is expected to offer subsidies to professionals dealing with the subject and to assist in the development of public health policies regarding interventions for the families of elderly with dementia.